The LiiNK Project®: Comparisons of Recess, Physical Activity, and Positive Emotional States in Grades K-2 Children - Clark, Laura E.; J. Rhea, Deborah (International Journal of Child Health and Nutrition, 2017)
The purpose of this study was to explore the physical activity patterns and emotional states differences among elementary school students at two private schools with differently structured school days. Students at one school received the LiiNK Project® pilot intervention, which included an additional two 15-minute recess breaks (unstructured outdoor play) throughout the school day and a 15-minute character development lesson three to four times weekly. Students at the comparison school received only one 30-minute recess daily and no additional character development curriculum. Grades K-2 children from two schools (N=262) wore pedometers for one school week and were observed for emotional expressions during recess. A univariate ANOVA revealed that intervention school students took significantly more steps on average than comparison school students, F(1, 260)=0.784, p<0.0001. Significant interactions were found for average number of steps between school and grade, F(2, 250)=4.298, p<0.05, school and gender, F(1, 250)=4.660, p<0.05, and grade and gender, F(2, 250)=6.919, p<0.001. Another univariate ANOVA revealed that during recess, intervention school students displayed significantly higher percentages of positive emotions than comparison school children, F(1, 52)=15.332, p<0.0001 and significantly lower percentages of not-positive emotions than comparison school students, F(1, 52)=13.900, p<0.0001. Overall, K-2 students who received multiple recesses and a character curriculum called Positive Action were significantly more active during the school day and displayed higher percentages of positive emotions on the playground than comparison school students.